The next one hundred years : shaping the fate of our living earth - Weiner, Jonathan. 4 0 16; 5 (New York : Bantam Books, 1990)
Details the state of our earth based on interviews with scientists and discusses the prospects for life on earth during the next 100 years.
Includes bibliographical references (p. 243-297).
Wilson's Senior High School;Library Journal;Booklist
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Influence on nature. -- Ecology.;Man;Biosphere.;Ecology.;Biosphere.;Human influence on nature; 20; 2